(untitled) (International journal of medical sciences, 2025)
Lichen planus is a pressing problem in dermatology due to the presence of severe forms of lichen planus, particularly those with a chronic course. Neoplastic transformation of lesions is possible, which is difficult to diagnose in atypical clinical forms of lichen planus.